Particulate Matter Emission from Combustion and Non-Combustion Automotive Engine Process: Review and Computational Bibliometric Analysis on Its Source, Sizes, and Health and Lung Impact - Nandiyanto, Asep Bayu Dani; Ragadhita, Risti; Setiyo, Muji; Obaidi, Abdulkareem Sh. Mahdi Al; Hidayat, Arif (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2023)
This study aimed to comprehensively analyze particulate matter (PM) emissions from vehicles, focusing on their sources based on combustion and non-combustion process, classification (PM10, PM2.5, PM0.1), and health implications (including PM transportation into lungs). Employing bibliometric analysis, we assessed the growth of scientific publications related to PM, identifying top-cited works based on citations, publisher, author, country, and affiliation. We also visually mapped the development of research in this field using keyword-based publication data from Scopus (2019-2023) with the keywords